Persistence of acute coronavirus disease 2019 infection: A rare case report - Anup Kumar Das,; Rajnish Kumar, (Indian Journal of Case Reports, 2020)
In late December 2019, the outbreak of coronavirus disease 2019 (COVID-19) caused by a novel coronavirus started in Wuhan, China, and has quickly spread globally. Clinical manifestations of COVID-19 have been shown to vary widely, from asymptomatic to acute respiratory distress syndrome, cardiovascular complications, and neurological symptoms such as acute inflammatory demyelinating polyneuropathy, gastrointestinal symptoms such as progression of compensated chronic liver disease to decompensated chronic liver disease. Here, we present the case of a 60-year-old symptomatic male who was tested COVID-19 positive on rapid antigen test (RAT) and reverse transcription-polymerase chain reaction (RT-PCR). The patient was given treatment as per protocol. The patient’s symptoms improved gradually but his RT-PCR and RAT were persistently positive till the 40th day of his hospital stay.